2010
DOI: 10.1007/s12291-010-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of Impaired Kidney Function with Serum Creatinine

Abstract: Serum creatinine (SCr) levels are frequently used as a screening test to assess impaired renal function; however, patients can have significantly decreased glomerular filtration rate (GFR) with normal SCr values and making the recognition of kidney dysfunction more difficult. Hence, this study was designed to determine the extent of misclassification of the patients who have significantly reduced GFR as calculated by reexpressed four variable modification of diet in renal disease (MDRD) equation but, normal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
3
11
1
Order By: Relevance
“…Related data portray systemic hypertension as being second only to diabetes mellitus as a cause of end stage renal disease (ESRD). Our records of a higher prevalence of decreased eGFR compared to that of increased serum creatinine correlates with the findings of Kannapiran et al [14] who observed 29.1% prevalence of glomerular filtration ≤60 mL/min/1.73 m 2 (MDRD) and 17.5% of increased serum creatinine [14], suggesting a possible under-representation of a diminishing renal capacity with the use of serum creatinine only as the tool for evaluating renal function [15,16]. This is probably a direct effect of the processes of creatinine generation, secretion and extrarenal excretion [14,17,18].…”
Section: Discussionsupporting
confidence: 92%
“…Related data portray systemic hypertension as being second only to diabetes mellitus as a cause of end stage renal disease (ESRD). Our records of a higher prevalence of decreased eGFR compared to that of increased serum creatinine correlates with the findings of Kannapiran et al [14] who observed 29.1% prevalence of glomerular filtration ≤60 mL/min/1.73 m 2 (MDRD) and 17.5% of increased serum creatinine [14], suggesting a possible under-representation of a diminishing renal capacity with the use of serum creatinine only as the tool for evaluating renal function [15,16]. This is probably a direct effect of the processes of creatinine generation, secretion and extrarenal excretion [14,17,18].…”
Section: Discussionsupporting
confidence: 92%
“…However, with SCr only 162 (17.5%) patients had abnormal renal function and SCr values misrepresented 108 (11.6%) patients with impaired kidney function. This discrepancy was even more pronounced either among female or older patients (1). A probable explanation for lower discrepancy between SCr and eGFR in their study (11.6% versus 27.3% in the present study) is using MDRD equation for calculating the patients' GFRs by them.…”
Section: Discussioncontrasting
confidence: 59%
“…Renal function assessment is critical in determining the eligibility or need to dose modification of nephrotoxic drugs in clinical practice (1). Measuring glomerular filtration rate (GFR) is a widely accepted index of renal function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further increase to 265 lmol/L reflects a decline of only 14 mL/min/ 1.73 m 2 [2,3]. It has been shown that 11 % of patients will have a serum creatinine in the reference range when their eGFR is \60 mL/min/1.73 m 2 [4].…”
Section: Introductionmentioning
confidence: 99%